2023
DOI: 10.3390/molecules28104184
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile, Antibacterial, Antibiofilm, and Antiviral Activities of Pulicaria crispa Most Potent Fraction: An In Vitro and In Silico Study

Abstract: Infectious diseases caused by viruses and bacteria are a major public health concern worldwide, with the emergence of antibiotic resistance, biofilm-forming bacteria, viral epidemics, and the lack of effective antibacterial and antiviral agents exacerbating the problem. In an effort to search for new antimicrobial agents, this study aimed to screen antibacterial and antiviral activity of the total methanol extract and its various fractions of Pulicaria crispa (P. crispa) aerial parts. The P. crispa hexane frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The analysis revealed significant bacterial activities of both extracts against various Gram-positive (Listeria monocytogenes, Staphylococcus aureus) and Gram-negative pathogenic bacteria (Acinetobacter baumannii, Escherichia coli, Pseudomonas aeruginosa). A similar finding was previously observed in P. crispa extracts [32]. In fact, the same authors reported that hexane fractions from P. crispa had antibacterial activities against four bacterial pathogens (S. aureus, Klebsiella pneumoniae, E. coli, and P. aeruginosa), with MIC values ranging from 62.5 to 125 µg/mL, and were able to affect influenza A virus at various stages of its lifecycle.…”
Section: Antibacterial Activitysupporting
confidence: 86%
See 1 more Smart Citation
“…The analysis revealed significant bacterial activities of both extracts against various Gram-positive (Listeria monocytogenes, Staphylococcus aureus) and Gram-negative pathogenic bacteria (Acinetobacter baumannii, Escherichia coli, Pseudomonas aeruginosa). A similar finding was previously observed in P. crispa extracts [32]. In fact, the same authors reported that hexane fractions from P. crispa had antibacterial activities against four bacterial pathogens (S. aureus, Klebsiella pneumoniae, E. coli, and P. aeruginosa), with MIC values ranging from 62.5 to 125 µg/mL, and were able to affect influenza A virus at various stages of its lifecycle.…”
Section: Antibacterial Activitysupporting
confidence: 86%
“…Bip. extracts induced various potencies on bacterial detachment from polystyrene surfaces [32]. It has been suggested that the interaction of the extracts is dependent on bacterial metabolism.…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…The poses of the compounds with the highest scores were selected. We utilized the Biovia discovery-studio 2020 visualizer to examine the representation of protein–ligand interactions in the active site of the complex [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…These include sterols like -sitosterol, stigmasterol, and lupeol; terpenes such as phytol; alkaloids like pulicarine and pulicaridine; flavonoids including quercetin, kaempferol, and luteolin; and phenols such as caffeic acid, chlorogenic acid, and gallic acid. These compounds have been associated with a range of biological activities, including antibacterial, antifungal, antiviral, antioxidant, anticancer, and anti-inflammatory effects [14,15]. To date, there has been a lack of research investigating the antimicrobial properties of an P. crispa extract against animal-sourced pathogens, despite its use as a grazing herb that is instinctively consumed by camels and small ruminants for its potential medicinal benefits.…”
Section: Introductionmentioning
confidence: 99%